2016
DOI: 10.3389/fmicb.2016.01098
|View full text |Cite
|
Sign up to set email alerts
|

Highly Effective Inhibition of Biofilm Formation by the First Metagenome-Derived AI-2 Quenching Enzyme

Abstract: Bacterial cell–cell communication (quorum sensing, QS) represents a fundamental process crucial for biofilm formation, pathogenicity, and virulence allowing coordinated, concerted actions of bacteria depending on their cell density. With the widespread appearance of antibiotic-resistance of biofilms, there is an increasing need for novel strategies to control harmful biofilms. One attractive and most likely effective approach is to target bacterial communication systems for novel drug design in biotechnologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 91 publications
0
51
0
4
Order By: Relevance
“…AI-2 is a product of SAM metabolism and may be indicative of the metabolic status of the cell and not present solely due to QS activity. Nevertheless, recent studies have shown that enzymes with AI-2 quenching capabilities have resulted in a significantly thinner biofilm that is more compact with a lower overall biovolume [58]. This finding suggests that, despite AI-2 having dual roles in both QS and metabolic pathways, quenching AI-2 may still be a good method to deter growth of unwanted bacterial populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI-2 is a product of SAM metabolism and may be indicative of the metabolic status of the cell and not present solely due to QS activity. Nevertheless, recent studies have shown that enzymes with AI-2 quenching capabilities have resulted in a significantly thinner biofilm that is more compact with a lower overall biovolume [58]. This finding suggests that, despite AI-2 having dual roles in both QS and metabolic pathways, quenching AI-2 may still be a good method to deter growth of unwanted bacterial populations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, by constructing large-insert cosmid libraries from metagenomes derived from various saline samples, enzymes displaying homologies to oxidoreductases, proteases, amidases, and aminotransferases were identified to exhibit a QQ effect against both AHL and AI-2 [58]. To exemplify, enzymes ranging from 177–478 aa that share close homology (42%–100% aa identity) with either aminotransferase, 3-hydroxy-2-methylbutyry-CoA dehydrogenase, ferredoxin reductase, 4-hydroxy-3-methybut-2-en-1-yl diphosphate synthase, 3-beta hydroxysteroid dehydrogenase, or N-acetylmuramoyl-L-alanine amidase were recovered from the Black Sea and salt marsh.…”
Section: Introductionmentioning
confidence: 99%
“…QQ assays on plates using strains AI1-QQ.1 and AI2-QQ.1 were performed with cell-free supernatants and cell extracts of fosmid clones and purified proteins as previously described in (25). In order to identify the respective ORFs of the fosmids conferring QQ activity, subcloning was used as previously described in (25,26). Putative QQ-ORFs were PCR-cloned into pMAL-c2X Nterminally fusing the QQ-ORFs to the maltose binding protein (MPB) using ORF-specific primers adding restriction recognition sites flanking the ORFs (see Tab.…”
Section: Identification and Molecular Characterization Of Quorum Sensmentioning
confidence: 99%
“…Putative QQ-ORFs were PCR-cloned into pMAL-c2X Nterminally fusing the QQ-ORFs to the maltose binding protein (MPB) using ORF-specific primers adding restriction recognition sites flanking the ORFs (see Tab. S1); overexpressed and proteins purified as recently described in (26).…”
Section: Identification and Molecular Characterization Of Quorum Sensmentioning
confidence: 99%
See 1 more Smart Citation